Xiexin Tang ameliorates dyslipidemia in high-fat diet-induced obese rats via elevating gut microbiota-derived short chain fatty acids production and adjusting energy metabolism. (15th September 2019) - Xiao, Suwei; Zhang, Zhimiao; Chen, Mengjun; Zou, Junfeng; Jiang, Shu; Qian, Dawei; Duan, Jinao
Abstract: Ethnopharmacological relevance: Traditional herbal medicine has been taken as a new and effective approach to treat many chronic diseases. Xiexin Tang (XXT), a compound recipe composed of Dahuang ( Rheum palmatum L.), Huangqin ( Scutellaria baicalensis Georgi) and Huanglian ( Coptis chinensis Franch.), has been reported to have hypoglycemic and hypolipidemic effects, but its mechanism remains unclear. Our previous study found that Xiexin Tang markedly ameliorated the composition of the gut microbiota, especially for some short chain fatty acids (SCFAs) producing bacteria, and then notably increased SCFAs production. However, the mechanism of XXT on the fermentation of gut bacteria and further improvement of obesity is not yet clear. Aim of the study: This study aimed to unravel the molecular mechanism of XXT on the amelioration of obesity. Materials and methods: Here, high-fat diet-induced obese rat model was established to investigate the intervention efficacy following oral administration of XXT. Additionally, the expressions of key enzymes of gut microbe-derived SCFAs biosynthesis and key targets in the signaling pathway of energy metabolism were investigated by ELISA and qPCR analysis. Results: Results showed that XXT could notably correct lipid metabolism disorders, alleviate systematic inflammation, improve insulin sensitivity and reduce fat accumulation. Additionally, XXT could increase gut microbiota-derived SCFAs-producing capacity by enhancing mRNA levels and activities of SCFA-synthetic key enzymes such as acetate kinase (ACK), methylmalonyl-CoA decarboxylase (MMD), butyryl-CoA: acetate CoA transferase (BUT) and butyrate kinase (BUK), which markedly decreased the adenosine triphosphate (ATP) contents, elevated adenosine diphosphate (ADP) and adenosine monophosphate (AMP) levels and further lowered the energy charge (EC) in obese rats via activating peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α)/uncoupling protein-2 (UCP-2) signaling pathway. What's more, XXT could notably ameliorate dyslipidemia via increasing the gene expression of 5′-AMP-activated protein kinase (AMPK) and blocking mammalian target of rapamycin (mTOR) signaling pathway. Conclusions: Taken together, our data provided a novel insight into the role of XXT in losing weight from energy metabolism regulation, which unraveled the molecular mechanism of XXT on the alleviation of dyslipidemia and fat heterotopic accumulation. The study provided useful information for XXT in clinical application to treat obesity. Graphical abstract: Image 1